2016
DOI: 10.3390/en9040253
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Production from Sweet Sorghum Juice at High Temperatures Using a Newly Isolated Thermotolerant Yeast Saccharomyces cerevisiae DBKKU Y-53

Abstract: Ethanol production at elevated temperatures requires high potential thermotolerant ethanol-producing yeast. In this study, nine isolates of thermotolerant yeasts capable of growth and ethanol production at high temperatures were successfully isolated. Among these isolates, the newly isolated thermotolerant yeast strain, which was designated as Saccharomyces cerevisiae DBKKU Y-53, exhibited great potential for ethanol production from sweet sorghum juice (SSJ) at high temperatures. The maximum ethanol concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
83
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(99 citation statements)
references
References 71 publications
(69 reference statements)
11
83
4
1
Order By: Relevance
“…In this study, SSJ supplemented only with (NH 4 ) 2 SO 4 was directly used by S. cerevisiae KKU-VN8 to produce ethanol, which differs from other conditions reported in the literature 3, 15, 24, 25, 26, 27, 28, 30, 66Table 6Comparison of ethanol production by S. cerevisiae KKU-VN8 and other yeast strains reported in the literatures.Strain S 0 (g/L)Sugar source T (°C) P (g/L)SC(%)T.Y.(%)Reference K. marxianus DMKU 3-1042220Sugar cane juice4067.8N/A60.4Limtong et al 3 I. orientalis IPE 100150Glucose4265.5N/A85.5Kwon et al 17 P. kudriavzevii DMKU 3-ET15180Cassava starch hydrolysate4078.6N/A85.5Yuangsaard et al 15 S. cerevisiae NRRL Y-2034200Sweet sorghum juice3070.6N/AN/APhutela and Kaur 67 S. cerevisiae AT-3180Glucose4068.590.075.0Tofighi et al 66 S. cerevisiae SEMF1185Sweet sorghum juice3386.297.391.9Zhao et al 28 S. cerevisiae DBKKU Y-53<...>…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study, SSJ supplemented only with (NH 4 ) 2 SO 4 was directly used by S. cerevisiae KKU-VN8 to produce ethanol, which differs from other conditions reported in the literature 3, 15, 24, 25, 26, 27, 28, 30, 66Table 6Comparison of ethanol production by S. cerevisiae KKU-VN8 and other yeast strains reported in the literatures.Strain S 0 (g/L)Sugar source T (°C) P (g/L)SC(%)T.Y.(%)Reference K. marxianus DMKU 3-1042220Sugar cane juice4067.8N/A60.4Limtong et al 3 I. orientalis IPE 100150Glucose4265.5N/A85.5Kwon et al 17 P. kudriavzevii DMKU 3-ET15180Cassava starch hydrolysate4078.6N/A85.5Yuangsaard et al 15 S. cerevisiae NRRL Y-2034200Sweet sorghum juice3070.6N/AN/APhutela and Kaur 67 S. cerevisiae AT-3180Glucose4068.590.075.0Tofighi et al 66 S. cerevisiae SEMF1185Sweet sorghum juice3386.297.391.9Zhao et al 28 S. cerevisiae DBKKU Y-53<...>…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, optimal conditions are determined with a second-order polynomial equation 29 . Many factors, including incubation temperature, initial yeast cell concentration, initial pH and sugar concentration, affect the growth and ethanol production of yeast cells 3, 11, 26, 30…”
Section: Introductionmentioning
confidence: 99%
“…Auesukaree et al [51] reported a strain C3867 that produced 38.8 g/L of ethanol at 41°C. Recently, Nuanpeng et al [52] and Techaparin et al [53] isolated S. cerevisiae DBKKUY-53 and KKU-VN8, respectively, in Thailand. The former strain produced the maximum ethanol concentration and volumetric ethanol productivity of 85.0 g/L and 2.83 g/L h, respectively, at 40°C, and the latter strain produced the maximum ethanol concentration of 89.3 g/L with a productivity of 2.48 g/L h and a theoretical ethanol yield of 96.3% from sweet sorghum juice at 40°C.…”
Section: Various Ethanologenic Thermotolerant Yeasts and Their Characmentioning
confidence: 99%
“…Ethanol tolerances also are known to be temperature subordinate [35]. Earlier researches have either centered on hereditary variety in either ethanol or temperature push however not both [42] [43] [44]. The two crosses contrasted in the other parent (YJF153 or SD1) and the impacts of the sensitive SEC24 and PSD1 alleles from HN6.…”
Section: Tropicalis Ctropicalis Tribeigelii Tribeigelii Blastcapimentioning
confidence: 99%